Outage performance of multi-RIS-assisted NOMA system with imperfect serial interference cancellation - Jiaqing QIN; Liping LUO; Jing ZHOU (物联网学报)
Considering the practical communication environments, the outage performance and the throughput were investigated for multiple reconfigurable intelligent surfaces (RIS) assisted non-orthogonal multiple access (NOMA) system with imperfect serial interference cancellation (SIC).The channel coefficients of the RIS-assisted NOMA system including the direct and the reflecting paths were approximated by Gamma distribution.An approximate closed-form expressions of outage probability were derived and validated through Monte Carlo simulations.The study investigated the relationship between the outage performance and system parameters, including the impact of imperfect SIC, the number of RIS and the number of reflecting units.The simulation results demonstrate that, compared with the single RIS-assisted NOMA and the traditional NOMA system, the multi-RIS-assisted system achieves a 14.2 dBm gain in signal-to-noise ratio (SNR) for a given outage probability.Thus, employing multiple RISs can improve the outage performance and the system throughput effectively, thereby compensating for the performance degradation caused by imperfect SIC.